PAYLATER TRANSACTIONS IN INDONESIAN E-COMMERCE: SHARIA BUSINESS PERSPECTIVE - Wahyudi, Tri Nur; Muhammad Sholahuddin; Henri Dwi Wahyudi; Muhammad Amir Anshori; Nur Ahmad; Sri Padmantyo; Imronudin (JURNAL ILMIAH EDUNOMIKA, 2025)
Engaging in financial transactions (muamalah) must adhere to sharia principles to ensure ethical and just practices, particularly in modern innovations such as PayLater systems. This study aims to analyze the alignment of PayLater transactions on Indonesian e-commerce platforms with sharia business principles. The research adopts a qualitative design with literature study approach. Data were collected through documentation methods, including journals, articles, and websites. The analysis was conducted using the Miles and Huberman model, involving three stages: data reduction, data display, and conclusion drawing. The findings indicate that PayLater transactions in Indonesian e-commerce platforms are largely inconsistent with sharia business principles. These inconsistencies include the presence of riba (usury) in the form of interest-based charges, gharar (uncertainty) in unclear contractual terms, violations of ba’i (trade ethics), and a lack of fairness in penalty structures. The study highlights the need for reforming PayLater systems to ensure compliance with Islamic principles and foster ethical financial practices.